Do banks crowd in or out business ethics? An indirect evolutionary analysis - Werner Güth (Humboldt University of Berlin, Interdisciplinary Research Project 373: Quantification and Simulation of Economic Processes, 1998)
The evolution of trustworthiness as a major aspect of business ethics depends crucially on whether it can be signaled. If this is impossible, only opportunistic traders will survive. Whereas previous studies have analysed detection agencies (Güth and Kliemt, 1994 and 1998) or have substituted signaling by ex post-punishment, e.g. in the form of courts (Brennan, Güth, Kliemt, 1997a and b), we here introduce the institution of banks which can guarantee payment. It is shown that this can crowd in trustworthiness, i.e. trustworthy traders can survive in the evolutionary race. Compared to detection agencies the result may, however, be both, crowding out and crowding in of business ethics. The crucial feature is the bank's ability to discriminate between trustworthy and unreliable debtors which, in our model, is formally captured by the probability difference of accepting their respective credit applications.
urn:nbn:de:kobv:11-10056837
Keywords: 330